INSTRUCTIONAL COMMUNICATION PATTERNS USED BY PASKIBRA EXTRACURRICULAR COACHES IN DEVELOPING STUDENT DISCIPLINE AT SMA NEGERI 1 HAMPARAN PERAK - Irham Prayoga; Suheri Harahap (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the instructional communication patterns of the flag-raising team coaches in fostering student discipline at SMA Negeri 1 Hamparan Perak and to identify communication barriers that arise during the training process. This study uses a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that the coaches' instructional communication patterns are structured through providing directions, delivering instructions, corrections, as well as evaluation and feedback. The communication applied not only serves to convey training instructions, but also fosters student discipline through instilling the values of responsibility, compliance with rules, and self-awareness. Discipline that initially emerged due to external control develops into internal awareness that is applied in academic and daily life. Communication barriers found include differences in member characters, varying levels of understanding, lack of focus, physical fatigue, and environmental factors. Therefore, structured and consistent instructional communication plays an important role in fostering student discipline in flagraising team extracurricular activities.